Hidden Cost In Building Conservation Works - Wee, Li Woon (2011)
More often than not, building conservation projects are usually completed with high cost and high time variances, which, in part is due to the uncertainty in actual work needed to conserve the building. Also, difficulty exists for cost estimators who are unfamiliar with building conservation works to estimate accurately. Realising the predicament in producing an accurate estimate, a study was conducted to identify the hidden costs of building conservation works, specifically the work items that contribute to such hidden cost and the factors affecting the cost overruns. A total of 16 respondents who have been involved in building conservation projects in Malaysia are surveyed using postal questionnaire. A total of thirty (30) work items that are specific to building conservation works are identified from the survey. Based on the results, these 30 special work items are grouped into four main categories, namely Research and Documentation, Scientific Studies, Laboratory Tests and Temporary Works. From the survey, work items such as ‘Carbonation Test’, ‘NIPGAT Test’, ‘Petrography Test’, and ‘Covermeter Survey’ are found to have the highest Relative Index value. Additionally, a total of 32 factors are also surveyed to detect the determinants of hidden costs in building conservation works. Dominant variables which are causing hidden costs include ‘lack of estimator’s expertise in conservation work’ and ‘lack of communication between consultants’. This study concludes with a list of work items encountered in building conservation works for quantity surveyor’s reference to prepare the cost estimate in future.